Pengaruh Minat Membaca Terhadap Keterampilan Berbicara Siswa Tingkat Sekolah Dasar (SD): A Literature Review - Vipassana, Vania; Dadi Satria (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to examine the relationship between reading interest and students' speaking skills at the elementary school level using a literature review approach. The background of this study focuses on the importance of reading interest as an element of speaking skills that need to be honed from an early age, and there is a strong assumption that reading interest has a major influence in improving these skills. The method applied is an analysis of five scientific articles found through a search using the keywords "speaking skills", "vocabulary", and "reading interest" on Google Scholar. The results of the study showed that all studies analyzed concluded that there was a significant and positive relationship between reading interest and speaking skills. Students who have a high interest in reading generally show better speaking skills thanks to their rich vocabulary, good sentence structure, and the ability to convey ideas regularly. These findings have important implications for teachers, curriculum developers, and parents to combine reading activities with speaking activities in the educational process. Increasing literacy culture from an early age has been shown to support the development of students' oral communication skills more effectively and sustainably.